Indonesian Trade Unions' Strategic Response to Unilateral Employment Termination during the COVID-19 Pandemic in Bekasi City/Regency - Ana Sabhana Azmy; Silmi Safriyantini (Universitas Medan Area, 2023)
This article investigates the resistance efforts of the All Indonesia Chemical Energy and Mining Workers Union (SP KEP SPSI) Bekasi in advocating for changes in cases of unilateral employment termination (PHK) at PT. Matahari Alka during the 2021 Covid-19 pandemic. This research primarily focuses on the analysis of SP KEP SPSI Bekasi's strategies and their success in challenging unilateral layoffs at PT. Alka Sun. Employing a qualitative approach, along with interviews conducted with SP KEP Bekasi Branch and Work Unit administrators within the company, this study, guided by Calvin Mackenzie's interest group strategy theory and Douglas McAdam's social movements theory, generates significant insights. The resistance undertaken by SP KEP SPSI Bekasi was rooted in the company's violations against workers, including unilateral layoffs that diverged from collective work agreement (PKB) provisions, non-payment of wages, and the prohibition of union activities. SP KEP SPSI's strategy encompassed demonstrations, lobbying of relevant authorities, and dialogue-based negotiations. The success of SP KEP SPSI Bekasi's strategy was closely linked to factors such as solidarity, which served as a foundation for strengthening the organization during these mobilizations, the union's capacity to motivate its members, and the formation of alliances.